LITHUANIAN PERSONAL BIBLIOGRAPHIC PUBLICATIONS IN SOVIET PERIOD - RAUDYTĖ, NIJOLĖ (Knygotyra, 2012)
The article deals with the analysis of Lithuanian personal bibliographic publications issued within the period of 1948–1989. The analysis was performed by the author who followed statistical and analytical principles and it revealed the specifics of subjects, objects and results of this field of bibliographic activity. In Soviet times the number of personal bibliographic publications constantly increased and both professional and non-professional bibliographic work was carried out in an active way. The analysis of contents of personal bibliographic publications demonstrated that in the Soviet period great attention was drawn to preparation and issue of personal bibliographic publications covering such spheres of activity as philological sciences, fiction and historical sciences. It was found out that the axiological function (regarding value and orientation) of personal bibliographic information was based on a social and pedagogic aspect peculiar to the analyzed period. The personal bibliographic information prepared in the Soviet period nowadays may successfully perform the cognitive, scientific research and socialization functions. Thus, we see that the major part of personal bibliographic publications issued in the Soviet period have survived and were left in Lithuanian libraries though they underwent strong “cleaning of stacks” in the first years of Independence and today they are used in case of necessity what proves their importance as of the source of history of science and culture. The article is aimed at carrying out the analysis of preparation, publishing and changes in the structure of Soviet-time personal bibliographic publications. The results of the analysis can be useful for science historians and specialists of bibliographic work.